2013
DOI: 10.1371/journal.pone.0053667
|View full text |Cite
|
Sign up to set email alerts
|

Risk for Eating Disorders Modulates Startle-Responses to Body Words

Abstract: Body image disturbances are core symptoms of eating disorders (EDs). Recent evidence suggests that changes in body image may occur prior to ED onset and are not restricted to in-vivo exposure (e.g. mirror image), but also evident during presentation of abstract cues such as body shape and weight-related words. In the present study startle modulation, heart rate and subjective evaluations were examined during reading of body words and neutral words in 41 student female volunteers screened for risk of EDs. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…At the neurofunctional level, Citron et al ( 2014 ) recently reported evidence for this perspective showing greater neural activation within right insular cortex in response to stimuli evoking conflicting approach-withdrawal tendencies (i.e., positive high-arousal and negative low-arousal words; PosHi; NegLo) compared to stimuli evoking congruent approach vs. withdrawal tendencies (i.e., positive low-arousal and negative high-arousal words; PosLo; NegHi). Further supporting evidence comes from ERP studies in favor of the approach-withdrawal assumption and the idea of the emotional and motivational embodiment of words (Herbert and Kissler, 2010 ; Herbert et al, 2012 , 2013 ).…”
Section: Toward a Neurocomputational Model Of The Vdt And Affective Wmentioning
confidence: 98%
See 2 more Smart Citations
“…At the neurofunctional level, Citron et al ( 2014 ) recently reported evidence for this perspective showing greater neural activation within right insular cortex in response to stimuli evoking conflicting approach-withdrawal tendencies (i.e., positive high-arousal and negative low-arousal words; PosHi; NegLo) compared to stimuli evoking congruent approach vs. withdrawal tendencies (i.e., positive low-arousal and negative high-arousal words; PosLo; NegHi). Further supporting evidence comes from ERP studies in favor of the approach-withdrawal assumption and the idea of the emotional and motivational embodiment of words (Herbert and Kissler, 2010 ; Herbert et al, 2012 , 2013 ).…”
Section: Toward a Neurocomputational Model Of The Vdt And Affective Wmentioning
confidence: 98%
“…These studies show that the BAWL is a popular tool for bridging the language—emotion gap in research and that its stimuli are well cross-validated at the three relevant processing levels: experiential (e.g., subjective ratings, self-reports; Võ et al, 2006 ; Schnitzspahn et al, 2012 ), behavioral and psychophysiological (e.g., response times, heart rate, startle reflex, oculo- and pupillometric responses; Kuchinke et al, 2007 ; Võ et al, 2008 ; Bayer et al, 2011 ; Briesemeister et al, 2011a , b ; Herbert et al, 2013 ), and neuronal (fMRI, EEG, fNIRS, and TMS or tDCS; Kuchinke et al, 2005 , 2006 ; Hofmann et al, 2009 ; Conrad et al, 2011 ; Bayer et al, 2012a , b ; Schlochtermeier et al, 2013 ; Tempel et al, 2013 ; Weigand et al, 2013a , b ; Briesemeister et al, 2014a , b ; Gärtner and Bajbouj, 2014 ; Hsu et al, 2014 ; Recio et al, 2014 ), as well as in computational-information technological and cartographic studies (Pak and Paroubek, 2010 ; Garcia Becerra, 2012 ; Hauthal and Burghardt, 2014 ).…”
Section: The “Berlin Affective Word List” (Bawl) As a Basic Tool For mentioning
confidence: 99%
See 1 more Smart Citation
“…Even though these studies do show that interactions between emotional, mental, and cognitive processing are accompanied by cardiac changes, regarding emotion and language processing, only a few studies have investigated stimulus-driven changes in mean HR during processing of emotional words. The studies available used a mix of spoken or written (synthesized) words, sentences, and stories, in combination with autobiographical imagery, recall, or cognitive instructions ( Vrana et al, 1986 ; Ilves and Surakka, 2012 ), or presented highly selective self-relevant stimulus materials such as threat words or body words to particular samples of individuals at risk for anxiety ( Thayer et al, 2000 ) or eating disorders ( Herbert et al, 2013b ), impeding the generalizability of the results.…”
Section: Introductionmentioning
confidence: 99%
“…When actual food items, rather than pictures of food, are presented, startle can be decreased in their presence (Hawk et al, 2004), unless the participant is told that the food item, though present in the testing room, would not be available for consumption until several hours later (Rejeski et al, 2010). Startle has also been used to investigate emotional reactivity to body image information, both in pictures (Spresser et al, 2012) and in words (Herbert et al, 2013).…”
Section: Eating Disordersmentioning
confidence: 99%